Release of adsorbed copper and carbon during Fe(Ⅱ) catalytic conversion of ferrihydrite-humic acid coprecipitation under acidic condition: Mechanism and properties. Issue 2 (April 2023) - Li, Yuanhang; Sun, Yuheng; Shi, Lei; Gong, Xiaofeng
Abstract: The mobility of copper (Cu) may be significantly impacted during the conversion of ferrihydrite-humic acid (Fh-HA) coprecipitates. However, the environmental behavior of the adsorbed Cu in Fh-HA coprecipitation and the kinetic process of organic carbon (C) during the Fe(Ⅱ)-catalyzed Fh-HA coprecipitates conversion remains unclear. In this study, a series of Fh-HA coprecipitates with various C/Fe molar ratios were synthesized. Furthermore, the effects of the Fe(Ⅱ) mediated Fh and Fh-HA conversion processes on Cu mobility and carbon release characteristics under acidic condition were investigated. The results show that the specific surface area of Fh-HA is reduced as compared to pure Fh, which impedes the conversion of Fe minerals and increases the release of Cu to the solution. The rate of conversion can be accelerated by increasing the Fe(II) concentration, resulting in the retention of Cu in the mineral structure. As compared to artificial HA, Elliott soil humic acid (ESHA) coprecipitated with Fh resulted in a reduced Cu release. According to results of the fluorescence excitation emission matrix-parallel factor analysis, the "release-resorption" process of carbon occurred during conversion and low molecular weight HA related to the biological activity was the main source of the released organic carbon. The major functional groups were C-O functional groups and phenolic hydroxyl groups, and Cu was involved in the formation of Fe-O-Cu after conversion. The findings of this study provide crucial information for comprehending the biogeochemical process of Cu associated with Fh and Fh-HA coprecipitates. Graphical Abstract: ga1 Highlights: Ferrihydrite conversion was inhibited with the increase of OC/Fe in coprecipitates. Fe(Ⅱ) promoted the stabilization of adsorbed Cu in coprecipitates during conversion. The "release-resorption" process of C occurred during conversion. Phenolic-OH was the main group in ferrihydrite-humic acid coprecipitates after conversion. Cu mainly existed in the formation of Fe-O-Cu after conversion.